CORRELATION BETWEEN SYSTEMIC LUPUS ERYTHEMATOSUS DISEASE ACTIVITY AND LUPUS RETINOPATHY USING MEX-SLEDAI SCORE - Seravina Adila Izzati; Ovi Sofia; Cesarius Singgih Wahono; Nadia Artha Dewi; Ovi Sofia (Indonesian Vitreoretinal Society, 2021)
Introduction: Lupus retinopathy and posterior uveitis are complications due to systemic lupus erythematosus which can threaten the vision. The presence of posterior segment manifestation is suggestive of high disease activity. The aim of this study is to identify posterior segment manifestation (Lupus Retinopathy and Posterior Uveitis) in SLE patient and their correlation with SLE disease activity using The Mexican-SLEDAI (MEX-SLEDAI) score. Methods: This was an analytical observational study with cross-sectional design, conducted from August to October 2020 and involved 114 SLE patients in Dr. Saiful Anwar General Hospital. We calculated MEX-SLEDAI score to assess SLE disease activity. All participant that met inclusion criteria underwent ophthalmology examinations using a portable slit-lamp, head indirect ophthalmoscope, and fundus finding were documented using portable fundus imaging. Result: Lupus retinopathy (LR) presents in 25/114 (21.9%) and posterior uveitis (PU) occurs in 2/114 (1.8%) SLE patients. The mean age of patient with LR, PU, and without retinopathy were 32.92; 37.00; and 31.08 years respectively. The posterior segment findings were hemorrhages, cotton wool spots, hard exudates, and vasculitis reflecting vascular damage. The most common manifestation found in retina was cotton wool spot. The mean of MEX-SLEDAI score of SLE patient with LR (7.200 ± 3.905) and SLE patient with PU (3.500 ± 2.121) was higher than the mean of SLE patient without LR and PU (2.871 ± 2.534). There was a significant association between LR and MEX-SLEDAI score (p=0.000). An insignificant association between PU and MEX-SLEDAI score was found (p=0.353) Conclusion There is a significance correlation between lupus retinopathy and SLE disease activity based on MEX-SLEDAI scores. The mean of MEX-SLEDAI score in SLE patients with lupus retinopathy was higher than SLE with posterior uvetis and SLE without posterior segment manifestations.